ANTHROPOMETRIC COMPARISON OF NASAL PARAMETERS IN MALE AND FEMALE STUDENTS-A CROSS-SECTIONAL STUDY - Acharya Sunita; Shrivastava Bhavana; Bharambe Vaishaly Kishore; Medatwal Bhupesh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Nasal anthropometry is a study that deals with the measurements of the proportion, size and shape of nose. The variability in size and shape of human nose is huge and is influenced by factors like age, sex, environment, ethnicity and region. The nasal index is an important anatomical tool that can be used to figure out sexual, racial and ethnic differences. The knowledge about the dimensions of the nose viz length and width are important for the reconstructive, aesthetic surgeries and personal identification for forensic purpose. Aim: The aim of study was to measure and compare the nasal parameters in male and female students. Material and methods-This cross-sectional study was conducted on 100 healthy volunteers (50 males and 50 females) aged between 17-25 years, in the Department of Anatomy, Pacific Institute of Medical Sciences, Umarda, Udaipur, Rajasthan, India. The nasal height and nasal width were measured using digital vernier caliper and nasal index were calculated. Results: In the present study the mean values for the male students were significantly higher than that of female students (P value<0.05). The major type of nose in males was mesorrhine (56%) and in females most common type of nose was leptorrhine (58%). Conclusion: The findings of the present study concluded that there were statistically significant differences found in nasal height, width and nasal index of male and female students.